2004
DOI: 10.1162/089892904322926719
|View full text |Cite
|
Sign up to set email alerts
|

All Talk and No Action: A Transcranial Magnetic Stimulation Study of Motor Cortex Activation during Action Word Production

Abstract: Abstract& A number of researchers have proposed that the premotor and motor areas are critical for the representation of words that refer to actions, but not objects. Recent evidence against this hypothesis indicates that the left premotor cortex is more sensitive to grammatical differences than to conceptual differences between words. However, it may still be the case that other anterior motor regions are engaged in processing a word's sensorimotor features. In the present study, we used single-and paired-pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
77
4
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 44 publications
14
77
4
2
Order By: Relevance
“…One may therefore argue that the language-induced effects we found on movement preparation/execution could be explained by this grammatical class confound. However, considering previous studies that showed similar cortical activations over the motor cortex for action-related nouns and verbs (but not for action-related and visually-related nouns; Oliveri et al, 2004;Pulvermüller et al, 1999b), we suggest that our results are more plausibly explained by semantic differences between word categories (action-and non-action-related).…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…One may therefore argue that the language-induced effects we found on movement preparation/execution could be explained by this grammatical class confound. However, considering previous studies that showed similar cortical activations over the motor cortex for action-related nouns and verbs (but not for action-related and visually-related nouns; Oliveri et al, 2004;Pulvermüller et al, 1999b), we suggest that our results are more plausibly explained by semantic differences between word categories (action-and non-action-related).…”
Section: Discussionsupporting
confidence: 44%
“…Two major models, the first based on Hebbian learning (Pulvermüller, 1996(Pulvermüller, , 2001(Pulvermüller, , 2005 and the second on the existence of the "mirror neuron system" (Fadiga & Craighero, 2004;Gallese & Lakoff, 2005;Rizzolatti & Arbib, 1998;Rizzolatti et al, 2001), suggest that processing of action words relies on activation of the motor programs used to perform, observe or simulate the actions referred to by words, either because of correlation learning (Pulvermüller, 2005) or because of a predisposition for imitation learning (Rizzolatti & Arbib, 1998). Evidence for such shared representations between word processing and sensory-motor information is provided by a large range of empirical data (Aziz-Zadeh et al, 2006;Boulenger et al, 2006;Boulenger et al, in press;Buccino et al, 2005;Glenberg & Kaschack, 2002;Glover et al, 2004;Hauk et al, 2004;Nazir et al, in press;Oliveri et al, 2004;Pulvermüller et al, 2005ab;Tettamanti et al, 2005;Zwaan & Taylor, 2006;see Fischer & Zwaan, in press, for a recent review). fMRI studies, for instance, have demonstrated somatotopic activation of motor and premotor cortices during processing of words or sentences referring to actions performed with arm, face or leg (AzizZadeh et al, 2006;Hauk et al, 2004;Tettamanti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, cortical motor regions are activated during processing of action-related language (Boulenger, Roy, Paulignan, Déprez, Jeannerod & Nazir, in press;Buccino, Riggio, Melli, Binkofski, Gallese & Rizzolatti, 2005;Hauk et al, 2004ab;Oliveri, Finocchiaro, Shapiro, Gangitano, Caramazza, & Pascual-Leone, 2004;Pulvermüller et al, 2005b;Pulvermüller, Hauk, Nikulin, & Ilmoniemi, 2005c;Shtyrov et al, 2004;Tettamanti et al, 2005). In a recent study, we could show that this language-related motor activity is significant to a point that it can interfere with the concurrent execution of overt motor behavior (Boulenger et al, in press).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to this outcome, a number of studies using TMS have observed positive congruency (i.e., facilitating) effects on the motor system induced by verbs denoting physical actions. For example, Papeo, Vallesi, Isaja, and Rumiati (2009) found that evoked potentials were enhanced in muscles of the hand when TMS was applied to the motor cortex and the language task incorporated verbs denoting hand actions (see also Oliveri et al, 2004).…”
mentioning
confidence: 99%